2017
DOI: 10.1159/000485409
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Functional Gastrointestinal Disorders: A Holistic Overview

Abstract: Background and Summary: Traditionally, functional gastrointestinal disorders (FGID), including functional dyspepsia or irritable bowel syndrome (IBS), are defined by more or less specific symptoms and the absence of structural or biochemical abnormalities that cause these symptoms. This concept is now considered to be outdated; if appropriate tests are applied, structural or biochemical abnormalities that explain or cause the symptoms may be found in many patients. Another feature of FGID are the highly preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 81 publications
5
102
0
16
Order By: Relevance
“…Increased mucosal permeability is one pathogenetic pathway of FGID . Claudins are important as TJ proteins .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased mucosal permeability is one pathogenetic pathway of FGID . Claudins are important as TJ proteins .…”
Section: Discussionmentioning
confidence: 99%
“…Increased mucosal permeability is one pathogenetic pathway of FGID. [35][36][37] Claudins are important as TJ proteins. 38 Vanheel et al found significantly lower expression of occludin but not of claudin-3 and claudin-4, and expression of ZO-1, beta-catenin, and Ecadherin at junctions was significantly lower in patients with FD.…”
Section: Accumulated Data Indicated That Eosinophils and Mast Cells Canmentioning
confidence: 99%
“…Despite increasing knowledge about potential mechanisms such as gut dysfunction, hypersensitivity, changes in membrane permeability, disturbed gut motility, low-grade inflammation, alteration in microbiota, and disturbances in brain-gut axis, many questions about IBS pathophysiology remain open. 10 Some risk factors for the development of IBS are well established: Young age and female sex are demographic risk factors. 9,11 Female predominance in prevalence during the first 60-70 years of life and a dissolution of this gender difference in people aged >65 years suggest an influence of gonadal sex hormones on IBS.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Despite increasing knowledge about potential mechanisms such as gut dysfunction, hypersensitivity, changes in membrane permeability, disturbed gut motility, low‐grade inflammation, alteration in microbiota, and disturbances in brain‐gut axis, many questions about IBS pathophysiology remain open …”
Section: Introductionmentioning
confidence: 99%
“…Functional disorders are those in which the gastrointestinal (GI) tract looks normal but doesn't work properly [1]. They are the most common problems affecting the GI tract (including the colon and rectum).…”
Section: Introductionmentioning
confidence: 99%